Проблеми соціальної та екологічної безпеки життя і діяльності як чинник якості інженерної освіти - Демідова, Юлія Євгенівна (НТУ "ХПІ", 2015)
Актуальність питання соціальної та екологічної безпеки життя і діяльності полягає у створенні складової системи у контексті навчання культурі промислової безпеки та психології професійної діяльності. Це полягає в тому, щоб засвоєні знання студент міг не тільки відтворити, але й застосувати їх у майбутній професійній діяльності.

The urgency of the issue of social and environmental health and safety is to create a component of training in the context of safety culture and psychology of professional activity. It is learned that the knowledge of the students could not only play, but also to apply them in their future professional activities. The practical steps that will determine the improvement of methods of forming appropriate knowledge of security activities, the development of sustainable skills of safe work methods, the formation of a common safety culture at all levels of production of the algorithm are characterized in the article. It is important to show the connection of this area with the general direction of solving production problems: technical, social and economic. The authors note that such a problem becomes complex and must be realized not only in the study of the humanities and the social and psychological and pedagogical disciplines, but also in the process of training in the study of special subjects. It is shown that the main components of the system security knowledge generation activities are: professional and comprehensive safety training activities; possession of principles, methods and means of ensuring the safety and ability to find optimal solutions-based organizational, administrative and technical nature for each specific case, understanding the essence of the proposed solutions and their possible consequences. The authors note that formation of such a system of knowledge will determine the relation between the individual disciplines and subspecialties safety activities.
Problems of social and environmental activity and safety as a factor in the quality of engineering education
Keywords: вища технічна освіта; інженерна освіта; професійна підготовка; екологічна безпека життєдіяльності; соціальна безпека життєдіяльності; виробнича безпека; екологічна культура; ecological safety of life; social safety of life; industrial safety; ecological culture; method of forming knowledge; security activities; future professionals; teachers of high school